Automatic detection of mediastinal lymph nodes using 3D convolutional neural network - Paing, May Phu; Pintavirooj, Chuchart; Tungjitkusolmun, Supan; Win, Kyi Pyar; Hamamoto, Kazuhiko (My University, 2019)
Mediastinal lymph nodes are one of the most critical factors to identify the clinical stages of lung cancer. As the lymph nodes are low in attenuation and cluttering with various shapes and sizes, manual detection is usually error-prone and effort-intensive. This paper introduces a method for automatic detection of mediastinal lymph nodes by proposing three significant contributions. First, we constraint the detection area, mediastinal region, using greylevel thresholding. Next, we apply the watershed method and hessian eigenvalues to separate a cluster of lymph nodes. Finally, we build a three-dimensional convolutional neural network (3D CNN) to distinguish the actual lymph nodes from other false lesions. Our experiment is conducted using 70 CT exams containing 314 lymph nodes and achieved a favorable result with 94 % detection rate.
Keywords: Computed tomography; Convolutional neural network; Lung cancer; Lymph nodes